Mobilização, articulação e entrega das competências aos processos de trabalho : um estudo na indústria do aço - Santolin, Maristela Cóla (2006)
The present dissertation discusses the changes in the work processes from the family production system to the Toyotist system as a means of contextualizing the approach to competences. This is an important subject in the academic universe of administratio